The Effect of The Student Facilitator and Explaining (SFAE) Learning Model Reporting Techniques on Writing Skills - Atika Zikri; Afnita (Jurnal Syntax Transformation, 2024)
Indonesian is one of the main subjects in the world of education in Indonesia. Language skills in these subjects include aspects of listening, reading, listening, speaking, listening and writing. The type of research used is quantitative. This research is called quantitative because the research data is in the form of numbers and the analysis uses statistics. Quantitative research is based on the philosophy of positivism which emphasizes objective phenomena that are studied quantitatively or using numbers, statistical processing, structure, and controlled experiments, (Sukmadinata, 2010: 53). In this subchapter two things are described. First, the skill of writing news texts before using the Student Facilitator And Explaining model assisted by reporting techniques for grade VIII students of SMP Negeri 15 Padang.